Outliers and American vanguard art - Cooke, Lynne 1952- (National Gallery of Art, 2018)
Some 250 works explore three distinct periods in American history when mainstream and outlier artists intersected, ushering in new paradigms based on inclusion, integration, and assimilation. The exhibition aligns work by such diverse artists as Charles Sheeler, Christina Ramberg, and Matt Mullican with both historic folk art and works by self-taught artists ranging from Horace Pippin to Janet Sobel and Joseph Yoakum. It also examines a recent influx of radically expressive work made on the margins that redefined the boundaries of the mainstream art world, while challenging the very categories of "outsider" and "self-taught." Historicizing the shifting identity and role of this distinctly American version of modernism's "other," the exhibition probes assumptions about creativity, artistic practice, and the role of the artist in contemporary culture. The exhibition is curated by Lynne Cooke, senior curator, special projects in modern art, National Gallery of Art....Provided by publisher